2017
DOI: 10.1039/c7cy01118k
|View full text |Cite
|
Sign up to set email alerts
|

CO2 hydrogenation to higher hydrocarbons on K/Fe–Al–O spinel catalysts promoted with Si, Ti, Zr, Hf, Mn and Ce

Abstract: Si and Zr species grafted on Fe–Al–O catalysts act as an inhibitor and promoter, respectively, in CO2 hydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…Dorner et al observed that the addition of ceria to a Fe/Mn/K-alumina catalyst significantly improved performances for the hydrogenation of CO 2 to C 2 -C 5 olefins, due to ceria promotion of the RWGS reaction. A similar approach has been described by Samanta et al who added 5% Ce on a K/Fe-Al-O spinel observing an increase in selectivity for methane and light C 2 -C 4 with respect to the undoped catalyst (Samanta et al, 2017). Xie et al instead tested successfully a composite material constituted by a Pt/CeO 2 core (RWGS functionality) surrounded by a Co-mesoporous silica shell (FT functionality) (Xie C. et al, 2017).…”
Section: Co2 Hydrogenation To Value Added Chemicals Other Than Methanementioning
confidence: 91%
See 2 more Smart Citations
“…Dorner et al observed that the addition of ceria to a Fe/Mn/K-alumina catalyst significantly improved performances for the hydrogenation of CO 2 to C 2 -C 5 olefins, due to ceria promotion of the RWGS reaction. A similar approach has been described by Samanta et al who added 5% Ce on a K/Fe-Al-O spinel observing an increase in selectivity for methane and light C 2 -C 4 with respect to the undoped catalyst (Samanta et al, 2017). Xie et al instead tested successfully a composite material constituted by a Pt/CeO 2 core (RWGS functionality) surrounded by a Co-mesoporous silica shell (FT functionality) (Xie C. et al, 2017).…”
Section: Co2 Hydrogenation To Value Added Chemicals Other Than Methanementioning
confidence: 91%
“…An ideal catalyst for this process should be active for both RWGS and FT synthesis, thus making its design quite complicated (Porosoff et al, 2016; Guo et al, 2018; Li and van Veen, 2018). To overcome this issue, the approach is that of designing bifunctional catalysts that couple both RWGS and FT functionalities in a single material, and a few attempts have been made also with ceria-containing formulations (Dorner et al, 2011; Samanta et al, 2017; Xie C. et al, 2017). Dorner et al observed that the addition of ceria to a Fe/Mn/K-alumina catalyst significantly improved performances for the hydrogenation of CO 2 to C 2 -C 5 olefins, due to ceria promotion of the RWGS reaction.…”
Section: Co2 Hydrogenation To Value Added Chemicals Other Than Methanementioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of the formation of С2+ hydrocarbons during hydrogenation of СО2 is described through the intermediate formation of methanol and without the stage of methanol formation [110,111]. Hydrogenation of СО2 through intermediate methanol occurs in the presence of mainly copper-zinc catalysts with the formation of light alkanes as the main products with hydrogenation of alkenes [112,113]. According to the second mechanism, CO2 hydrogenation proceeds in two stages: the stage of the reverse reaction of the conversion of water gas (OCWG) and the Fischer-Tropsch synthesis (FT).…”
Section: Mechanism Of Co2 Hydrogenation To Hydrocarbonsmentioning
confidence: 99%
“…Metal oxides can also serve as structural and electronic promoters 68 . It was reported that SiO2, TiO2, ZrO2, HfO2, CeO2 and MnO2 might modify the texture and surface reactivity of The alkane selectivity was calculated based on all products except CO.…”
Section: Promotersmentioning
confidence: 99%